Robust H2 Power System Stabilizer Design With Norm-Bounded Parameter Uncertainties - syah, Hardian (ELKHA: Jurnal Teknik Elektro, 2011)
Abstract This paper addresses the design problem of robust H2 output feedback controller for damping power system oscillations. Sufficient conditions for the existence of output feedback controllers with norm-bounded parameter uncertainties are given in terms of linear matrix inequalities (LMIs). Furthermore, a convex optimization problem with LMI constraints is formulated to design the output feedback controller which minimizes an upper bound on the worst-case H2 norm for a range of admissible plant perturbations. The technique is illustrated with applications to the design of stabilizer for a single-machine infinite-bus (SMIB) power system. The LMI based control ensures adequate damping for widely varying system operating. Keywords H2 controller, linear matrix inequality, power system stabilizer, single-machine infinite-bus systems